1990
DOI: 10.1073/pnas.87.17.6772
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Halobacterium halobium: development of vectors and investigation of gas vesicle synthesis.

Abstract: We developed vector plasmids for the transformation of Halobacterium halobium, using the replicon region from the halobacterial phage OH or from' the plasmid pHHl together with a DNA fragment conferring resistance to mevinolin. H. halobium P03, a strain lacking pHHI as well as the restriction endonuclease activity found in wild-type H.halobium, was used as the recipient strain. AlR H. halobium fragments tested for autonomous replication as well as the Haloferax volcanii vector pWL102 enabled stable plasmid mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 17 publications
2
79
1
Order By: Relevance
“…In the case of the halophilic archaea, transformation experiments confirmed that the 14 different genes clustered in a region (the vac region) of approximately 9 kb are sufficient for the formation of gas vesicles (Vac+ phenotype) in the Vac-negative recipient, Haloferax volcanii (Blaseio & Pfeifer, 1990;Englert et al, 1992a, b). Hf.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the case of the halophilic archaea, transformation experiments confirmed that the 14 different genes clustered in a region (the vac region) of approximately 9 kb are sufficient for the formation of gas vesicles (Vac+ phenotype) in the Vac-negative recipient, Haloferax volcanii (Blaseio & Pfeifer, 1990;Englert et al, 1992a, b). Hf.…”
Section: Introductionmentioning
confidence: 89%
“…Shuttle vectors are available that harbour genes conferring resistance to mevinolin (Lam & Doolittle, 1989;Blaseio & Pfeifer, 1990) or novobiocin (Holmes et al, 1991), and compatible origins of replication. The vectors used for complementation studies with the Vac-recipient Hf.…”
Section: Introductionmentioning
confidence: 99%
“…Hfx. volcanii also has a restriction system that recognises adenine-methylated GATC sites (which occur frequently in vectors based on E. coli plasmids), resulting in DNA fragmentation followed by plasmid loss or chromosomal integration by recombination 63 . This can be circumvented by passaging the DNA through an E. coli dam -strain that is deficient in GATC methylation 64 .…”
Section: Transformationmentioning
confidence: 99%
“…1, according to Table 1. The PRC products were ligated to the halobacterial shuttle vector pUBP2, which has been described previously [12]. The vector was a gift from F. Pfeifer, Martinsried.…”
Section: Methodsmentioning
confidence: 99%